Oral lichen planus : a retrospective comparative study between Thai and Croatian patients - Thongprasom, Kobkan (Array, 2009)
Summary: Oral lichen planus (OLP) is a common oral mucosal disease that affects middle age patients. However, there are few reports about the incidence of OLP in different ethnic groups. The purpose of this study was to compare the characteristics of OLP in Thai and Croatian patients. Retrospective data were taken from medical records of 175 patients referred to the Oral Medicine Department of Chulalongkorn University and 175 patients referred to the School of Dental Medicine, University of Zagreb during the 1997- 2007 period. In all patients the diagnosis of OLP was clinically and histopathologically confirmed. In Thai and Croatian OLP patients, females were predominant (the female to male ratio was 3.5:1). Croatian OLP patients were older with a significant age difference between female Thai and Croatian OLP patients (p<0.05). Atrophicerosive type of OLP was common in Thai patients, whereas reticular OLP was predominant in Croatians (p<0.001). Burning sensation was the most common chief complaint in both ethnic groups. Significant differences between the two ethnic groups were found in the sites of OLP lesions as well as in the occurrence of pain, roughness and white patches, systemic diseases and use of medication (p<0.05). Croatian patients had more systemic diseases and took more medications than Thai. Three cases showed dysplasia in either group, whereas only one Thai patient developed squamous cell carcinoma. Although Thai and Croatian patients differed significantly according to the clinical type of OLP, the rate of malignant transformation was very low